THE ANALYSIS OF PREPOSITIONAL PHRASE IN NOVEL ‘THE PERFECT NANY’ WRITTEN BY LEILA SLIMANI - Astri Thea Rahmanita; Ice Sariyati; Yuyun Nurulaen (CALL, 2019)
Prepositional Phrase is the part of preposition and absolutely it is the part of grammar too. It has rules and deregulations that must be obeyed. Without a correct replacement of preposition, the meaning of the sentence can make the people confused. Hence, the research questions of this research are: 1) What are the positions of prepositions phrase of sentences found in Novel The Perfect Nany written by Leila Slimani?. 2) What are the patterns of tree diagram for a prepositional phrase of sentences found in Novel The Perfect Nany written by Leila Slimani?. The researcher use Position of Prepositional Phrase theory by Frank (1972) and theory of a tree diagram by Delahunty and Garvey (2010) to analyze the data. The findings show that the position of prepositional phrase in novel The Perfect Nany written by Leila Slimani is dominated by position in adverbial function (34 data). And the position in adjectival function is only found with 16 data. Base on the data analysis, it can be concluded that prepositional phrase adverbial function is more widely used than prepositional phrase adjectival function, because it can modify the verb, adverb, and adjectival that are mostly found in sentences. It is was also concluded that in one sentence there could be more than one prepositional phrase through the tree diagram that have been analyzed.Key words: Prepositional Phrase, Adverbial Function, Adjectival Function